The Influence of japanese leadership style on employee performance and the Mediating Role of Employee Engagement at Japanese firm in Indonesia: Study among indonesian employee in japanese company - Maresa, Finesssya Nurul Sukma; Soeling, Pantius Drahen (Archives of Business Research, 2019)
Abstract There were tens of thousands of small scale enterprises (SSEs) operating within business environment in Nigeria, but continuous under-development, inability to access loanable funds, lack of innovation and weak capital base have characterized the informal market and chances of survival have become doubtful and bleak. To this extent, the study examined the impact of micro-credits financing on SSEs’ survival in an emerging market, Nigeria. Primary source of data was through questionnaire. A regression method - simple Ordinary Least Square (OLS) method was adopted to analyze the responses gathered through the research instrument. The result showed that R2 = 0.846, which explained the variations in SSEs survival by micro-credit behavioral funding pattern of micro-banks; while overall result was statistically significant (p˂0.05). The paper concluded that SSEs were often used as indices to measure the level of industrialization. The paper however recommended that policymakers and other stakeholders should consistently review policies guiding the establishment and operations of informal market in order to achieve the expected target of sustainability. Keywords: Small scale enterprises, Survival, Financing, Micro-credits, Nigeria.